expediency and corruption and good and bad; unity or contrast - Mohammadhasan Samooei; Seyed Mustafa Hosseini Nasab (اخلاق وحیانی)
Expediency and corruption in the term is the base of legislating Sharia rules. On the other hand, beauty and ugliness are concepts that have a long history in various sciences, and different meanings such as perfection and imperfection, agreement and disagreement with intent, deserving of praise and blame, reward and punishment have been considered for them. In the science of principles of jurisprudence, this question has been raised that what is the relationship between expediency and corruption as the basis of Sharia rulings with good and bad. Mohaghegh Esfahani believed that they are the same, and Martyr Sadr considered comparing these concepts with each other. This article aims to examine the relationship between these two types of concepts with a critical-analytical method. With the selected definition of good and bad, which expresses the relationship of necessity between the act and its result, we can understand the same thing between good and bad, expedient and corrupt.